Numerical analysis of anisotropic stiffness and strength for geomaterials - Fei Song; Manuel A. González-Fernández; Alfonso Rodriguez-Dono; Leandro R. Alejano (Journal of Rock Mechanics and Geotechnical Engineering, 2023)
In numerical modelling, selection of the constitutive model is a critical factor in predicting the actual response of a geomaterial. The use of oversimplified or inadequate models may not be sufficient to reproduce the actual geomaterial behaviour. That selection is especially relevant in the case of anisotropic rocks, and particularly for shales and slates, whose behaviour may be affected, e.g. well stability in geothermal or oil and gas production operations. In this paper, an alternative anisotropic constitutive model has been implemented in the finite element method software CODE_BRIGHT, which is able to account for the anisotropy of shales and slates in terms of both deformability and strength. For this purpose, a transversely isotropic version of the generalised Hooke's law is adopted to represent the stiffness anisotropy, while a nonuniform scaling of the stress tensor is introduced in the plastic model to represent the strength anisotropy. Furthermore, a detailed approach has been proposed to determine the model parameters based on the stress–strain results of laboratory tests. Moreover, numerical analyses are performed to model uniaxial and triaxial tests on Vaca Muerta shale, Bossier shale and slate from the northwest of Spain (NW Spain slate). The experimental data have been recovered from the literature in the case of the shale and, in the case of the slate, performed by the authors in terms of stress-strain curves and strengths. A good agreement can be generally observed between numerical and experimental results, hence showing the potential applicability of the approach to actual case studies. Therefore, the presented constitutive model may be a promising approach for analysing the anisotropic behaviour of rocks and its impact on well stability or other relevant geomechanical problems in anisotropic rocks.